Knowledge, attitudes and practices of evidence-based medicine in attending physicians of a public hospital. Lima Peru - Segundo-Paredes, Jorge Alfredo (2019)
Objective. Determine the knowledge, attitudes and practices in Evidence Based Medicine (EBM) in attending physicians of a public hospital. Materials and methods. Analytical observational cross-sectional design, a validated instrument with a Kuder and Richarson index (KR 20) of 0,79 was used. Results. The knowledge of MBE is low intermediate in 60% of the participants. In addition, there is a statistical association between the number of hours dedicated to the search for information and the level of knowledge of MBE. Conclusions. It is necessary to generate methodological strategies of medical education to improve the knowledge of the MBE to optimize the attitudes and practices of this medical activity.